Thermal-insulating porous material based on waste of mining and metallurgical industries - Barantseva, Svetlana E.; Klimosh, Yuriy A.; Azaranka, Iryna M.; Hundzilovich, Mikalai M.; Pospelov, Andrey V. (Journal of the Belarusian State University. Ecology, 2021)
Currently, an actual problem is the use of various industrial wastes to improve the environmental situation in the Republic of Belarus which allows not only saving natural raw materials, increasing production efficiency, but also contributing to the improvement of the environmental situation at factories and adjacent territories. Ceramic mass сompositions of the raw materials consisting of wastes from the mining and metallurgical industries, clay from the “Lukoml” deposit were developed as a result of the experimental studies. Ceramic masses were made for preparing raw granules and thermal-insulating materials were obtained with a set of required physical and mechanical characteristics – volumetric density, thermal conductivity, frost resistance, mechanical compressive strength.
Keywords: ecology; industrial waste; granitoid screenings; dust from gas cleaning units; porous structure; heat treatment; physical and chemical properties